2020
DOI: 10.53935/2641-533x.v3i3.145
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tertiary EFL Teachers’ Professional Identity on Job Burnout in Hubei Province China

Abstract: In order to explore the relationships of tertiary EFL teachers’ professional identity and job burnout, a quantitative survey was conducted on 565 tertiary EFL teachers in Hubei Province in central China. The results indicated that teachers with different educational background and teachers teaching different types of students experience different levels of burnout; Tertiary EFL teachers’ professional identity were significantly negatively related to their job burnout; The valence and self-presentation in profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…They argued that teacher self-efficacy mediates the correlation between teacher burnout and teacher professional identity. Zhao et al (2020) , in another study, found that Chinese teachers’ professional identity, particularly valence and self-presentation, are significantly and negatively correlated with teacher burnout. They argued that once instructors have the feeling that instruction is fascinating, and see the value in education, they are less likely to get bored in their job.…”
Section: Literature Reviewmentioning
confidence: 94%
“…They argued that teacher self-efficacy mediates the correlation between teacher burnout and teacher professional identity. Zhao et al (2020) , in another study, found that Chinese teachers’ professional identity, particularly valence and self-presentation, are significantly and negatively correlated with teacher burnout. They argued that once instructors have the feeling that instruction is fascinating, and see the value in education, they are less likely to get bored in their job.…”
Section: Literature Reviewmentioning
confidence: 94%